A business opportunity or dilemma? - Lau, Yeng Wai; Ng, Siew Imm (Universiti Putra Malaysia Press, 2011)
This case presents an opportunity for students of business degree programs to assess and make cross-country market expansion decisions. The case put forth a scenario where a Small-and-Medium size Enterprise (SME) made a cross-border geographic expansion decision where short-term financial gains took precedence. The importance of cross-country differences particularly in terms of management style and work culture was downplayed. The case has a low-to-moderate level of difficulty and can be used as part of the teaching materials in the International Business Management, Cross-cultural Management, Entrepreneurship, and Organizational Behavior discipline.